Frommer's Disney World, Universal & Orlando 2024 - Cochran, Jason (Frommer Media, 2024)
"Preparing for an Orlando vacation can be a full-time job, and it costs a small fortune. Most other books on the market make the problem worse, burying vacationers in endless pages of pointless details unquestioningly cheering for the high-priced theme parks and resorts. But this lightweight, fact-packed guide cuts through the noise and compresses the information you truly need to know. No other book does what we do: Honest talk, money-saving tips, and affectionate insider secrets to Walt Disney World, Universal Orlando, SeaWorld, and the inimitable culture and history of Orlando and Central Florida"--